Two dipole magnetic systems for technological electron accelerator - Bovda, V.А.; Bovda, А.М.; Guk, I.S.; Dovbnya, А.N.; Kononenko, S.G.; Lyashchenko, V.N.; Mytsykov, А.О.; Onishchenko, L.V. (Вопросы атомной науки и техники, 2019)
For a 10 MeV technological accelerator, a dipole magnet with a permanent magnetic field was created using the SmCo alloy. The maximum magnetic field in the magnet gap was 0.3 T. The magnet is designed to measure the energy of the beam and to adjust the accelerator for a given energy. For a linear accelerator with an energy of 23 MeV, a dipole magnet based on the Nd-Fe-B alloy was developed and fabricated. It was designed to rotate the electron beam at a 90 degrees. The magnetic field in the dipole magnet along the path of the beam was 0.5 T. The effective length of the magnet was 242 mm. Для технологічного прискорювача на енергію 10 МеВ створено дипольний магніт з постійним полем з використанням SmCo-сплаву. Максимальне поле в магніті дорівнює 0,3 Тл. Магніт призначений для визначення енергії пучка і настроювання прискорювача на задану енергію. Для лінійного прискорювача з енергією 23 МеВ розроблений і виготовлений дипольний магніт на основі Nd-Fe-B-сплаву. Він призначений для повороту пучка електронів на 90 градусів. Поле в магніті уздовж траєкторії руху пучка дорівнює 0,5 Тл. Ефективна довжина магніту дорівнює 242 мм. Для технологического ускорителя на энергию 10 МэВ создан дипольный магнит с постоянным полем с использованием SmCo-сплава. Максимальное поле в магните равно 0,3 Тл. Магнит предназначен для измерения энергии пучка и для настройки ускорителя на заданную энергию. Для линейного ускорителя с энергией 23 МэВ разработан и изготовлен дипольный магнит на основе Nd-Fe-B-сплава. Он предназначен для поворота пучка электронов на 90 градусов. Поле в магните вдоль траектории движения пучка равно 0,5 Тл. Эффективная длина магнита равна 242 мм.